PENERAPAN METODE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN (PKK) PADA SISWA KELAS XI MULTIMEDIA DI SMK NEGERI 5 MERANGIN TAHUN AJARAN 2022/2023 - Reni Kurniawati, S.Pd (LP3M | STKIP YPM Bangko, 2022)
This research is entitled “Application of the Talking Stick Method to Improve Learning Outcomes of Creative Products and Entrepreneurship (PKK) in Class XI Multimedia Students at SMK Negeri 5 Merangin for the 2022/2023 academic year. Based on the results of research at SMK Negeri 5 Merangin showed low student learning outcomes in the subjects of Creative Products and Entrepreneurship (PKK). The purpose of this study was to determine the application of the talking stick method in PKK learning outcomes. The object of this research is the students of class XI Multimedia A totaling 21 students. The method used is Classroom Action Research (CAR) by giving tests to students to measure student learning outcomes. Data analysis uses quantitative data analysis. The results show that: the talking stick method is effectively used in improving PKK learning outcomes for students in class XI Multimedia A. This can be seen from the increase in PKK learning outcomes for students from pre-cycle, Cycle I, and Cycle II. PKK learning outcomes of students from pre-cycle students who completed as much as 9.52% increased in the first cycle to 53.28%. Cycle I to cycle II classical student learning outcomes increased to 85.71%. Thus, the social studies learning outcomes of students from pre-cycle to cycle II increased by 76.19%.